(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2025)
The General Meeting of Shareholders (GMS) is the highest governing body in a company’s structure, holding exclusive authority that cannot be exercised by the board of directors and the board of commissioners. This authority includes approving the annual report, amending the articles of association, appointing and dismissing directors and commissioners, mergers, consolidations, acquisitions, company dissolution, and other strategic decisions that significantly impact the company’s continuity. The GMS consists of the Annual GMS and the Extraordinary GMS, each playing a crucial role in decision-making. This article discusses the exclusive powers of the GMS that are not held by the board of directors and the board of commissioners, highlighting its role in corporate governance and its impact on corporate transparency and accountability. Keywords: GMS, authority, board of directors, board of commissioners, corporate governance